2021
DOI: 10.1016/j.ajog.2020.12.632
|View full text |Cite
|
Sign up to set email alerts
|

611 Racial, ethnic and socioeconomic disparities in susceptibility to SARS-CoV-2 in pregnancy

Abstract: Previous studies suggest a relationship between ABO and Rh blood groups and susceptibility to SARS-CoV-2. Infection status in these studies was determined using polymerase chain reaction (PCR) from nasopharyngeal swabs. Antibody testing may be a more accurate method to assess susceptibility since it detects both current and past infection. Universal testing for SARS-CoV-2 in pregnant women, a generally healthy population, will more likely include a higher number of asymptomatic individuals. This is contrary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Screening has confirmed that the prevalence of infection is similar to that of the general population with regards to its regional and temporal course 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 . However, there are indications that some groups of female patients have a higher risk of infection based on their ethnicity 25 , 26 , 27 , 28 , 29 , 30 or socio-economic status 31 , 32 . A population-based British cohort study (3527 SARS-CoV-2 infections in 342 080 pregnant women) showed that SARS-CoV-2 infection occurred more often in women who were younger and were primipara, belonged to a non-white ethnic group, lived in disadvantaged areas, or had comorbidities 33 .…”
Section: Guidelinementioning
confidence: 99%
See 1 more Smart Citation
“…Screening has confirmed that the prevalence of infection is similar to that of the general population with regards to its regional and temporal course 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 . However, there are indications that some groups of female patients have a higher risk of infection based on their ethnicity 25 , 26 , 27 , 28 , 29 , 30 or socio-economic status 31 , 32 . A population-based British cohort study (3527 SARS-CoV-2 infections in 342 080 pregnant women) showed that SARS-CoV-2 infection occurred more often in women who were younger and were primipara, belonged to a non-white ethnic group, lived in disadvantaged areas, or had comorbidities 33 .…”
Section: Guidelinementioning
confidence: 99%
“…Screeninguntersuchungen bestätigen eine Prävalenz analog der Gesamtbevölkerung in Bezug auf regionale und zeitliche Verläufe 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 . Es bestehen jedoch Hinweise für ein höheres Infektionsrisiko unter bestimmten Patientinnengruppen in Abhängigkeit von der Ethnizität 25 , 26 , 27 , 28 , 29 , 30 oder dem sozioökonomischen Status 31 , 32 . Eine populationsbasierte britische Kohortenstudie (3527 SARS-CoV-2-Infektionen unter 342 080 Schwangeren) zeigte, dass eine SARS-CoV-2-Infektion häufiger bei Frauen auftrat, die jünger und erstgebärend waren, nichtweißen ethnischen Gruppen angehörten, in benachteiligten Gebieten wohnten oder Komorbiditäten aufwiesen 33 .…”
Section: Leitlinieunclassified
“…Im Vergleich zu nicht- hispanischen Patienten waren in einer US-amerikanischen Erhebung hispanische Patienten häufiger SARS-CoV-2-positiv (10,6 vs. 5,5%, aRR 1,73; 95% KI 1,05–2,85), ebenso wie Patienten mit öffentlicher Versicherung im Vergleich zu privat Versicherten (9,5 vs. 2,5%, aRR 3,11; 95% KI 1,12–8,64) 130 . Die Suszeptibilität für SARS-CoV-2 in der Schwangerschaft kann neben der ethnischen Zugehörigkeit auch durch sozioökonomische Faktoren beeinflusst werden 131 132 .…”
Section: Hintergrundinformationen Zu Sars-cov-2 Und Covid-19 In Der S...unclassified